Comparative Susceptibility Study Against Pathogens Using Fermented Cranberry Juice and Antibiotics - Mantzourani, Ioanna; Bontsidis, Christos A.; Plessas, Stavros; Alexopoulos, Athanasios; Theodoridou, Eirini; Tsigalou, Christina; Voidarou, Chrysa; Douganiotis, George; Kazakos, Stavros L.; Stavropoulou, Elisavet; Bezirtzoglou, Eugenia (Frontiers in Microbiology, 2019)
In the present study, unfermented and fermented cranberry juice in combination with the Antibiotics vancomycin and tigecycline were tested for their antimicrobial activity. Cranberry juice was fermented with a recently isolated potentially probiotic Lactobacillus paracasei K5. The tested strains selected for this purpose were Enterococcus faecalis, E. faecium, Enterobacter cloacae and Staphylococcus aureus. The methods followed were the determination of zones inhibition, Minimum Inhibitory Concentration (MIC) and Fractional Inhibitory Concentration Index (FICI). Tigecycline together with fermented juice exhibited larger Zones of Inhibition (ZOI) in strains of E. faecium (65 ± 4.8 mm) compared to the respective ZOI with tigecycline and unfermented juice (no zone). The same outcome was also obtained with E. cloacae. Vancomycin together with fermented juice exhibited larger ZOI in strains of E. faecium (28 ± 2.2 mm) compared to the respective ZOI with vancomycin and unfermented juice (24 ± 2.3 mm). The lowest MIC values were recorded when tigecycline was combined with fermented cranberry juice against S. aureus strains, followed by the same combination of juice and antibiotic against E. cloacae strains. FICI revealed synergistic effects between fermented juice and tigecycline against a strain of E. faecium (A2020) and a strain of E. faecalis (A1940). Such effects were also observed in the case of fermented juice in combination with vancomycin against a strain of S. aureus (S18), as well as between fermented juice and tigecycline against E. cloacae (E1005 and E1007) strains. The results indicate that the antibacterial activity of juice fermented with the potentially probiotic L. paracasei K5 may be due to synergistic effects between some end fermentation products and the antibiotic agents examined.